Bullying Experiences, Anxiety About Bullying, and Special Education Placement - Saia, Danielle M.; Saylor, Conway F.; Allen, Ryan A.; Arnau, Penny L. (Journal of the American Academy of Special Education Professionals, 2009)
Bullying experiences and self-reported anxiety about bullying and were compared in 72 elementary and middle school students including 16 in self contained (SC) special education classes, 20 receiving resource or consultation (RC), and 36 matched peers. Individually administered Bully Victimization Scale and School Violence Anxiety Scale scores (Reynolds, 2003) revealed that children with special needs (both SC & RC) tended to report more peer victimization and higher anxiety about school violence than matched peers from the same schools. Placement was not related to self-reported bullying experiences. Students in self-contained classes were significantly more anxious about possible bullying, especially physical, in spite of being in more protected environments. School placement is an important but under-researched issue in assessment and intervention for bullying of students receiving special education services.